2022
DOI: 10.3390/s22135058
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Image Processing Method to Improve Autofocusing Accuracy

Abstract: For automated optical inspection, autofocusing microscopes play an important role in capturing clear images of the measured object. At present, the image processing part of optics-based autofocusing microscopes often has various factors, which makes it impossible to describe the image information of the semicircular (or elliptical) spot with a simple circle-finding method. Accordingly, this study has developed a novel algorithm that can quickly calculate the ideal center of the elliptical spot and effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Impressively, this challenge is effectively addressed through the use of a sole offset lens, achieving accuracy within 3 µm without the need for supplementary compensation systems or costly optics. Furthermore, compared to previous research [19], this system introduces improvements that specifically focus on the region near the focal point, utilizing a pre-established knife-edge centroid method. In prior studies, the issue of light spot deformation had not been addressed; however, in the course of our research, we further tackled this previously unmentioned concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impressively, this challenge is effectively addressed through the use of a sole offset lens, achieving accuracy within 3 µm without the need for supplementary compensation systems or costly optics. Furthermore, compared to previous research [19], this system introduces improvements that specifically focus on the region near the focal point, utilizing a pre-established knife-edge centroid method. In prior studies, the issue of light spot deformation had not been addressed; however, in the course of our research, we further tackled this previously unmentioned concern.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it's crucial to acknowledge that the optics-based autofocus method might be susceptible to environmental factors that could potentially impact the accuracy of the focus, as indicated by some studies [15]. Currently, numerous researchers are dedicated to enhancing the accuracy of optical autofocus, whether through improving hardware components [16,17] or employing advanced image processing techniques [1,[18][19][20][21][22]. Despite the beneficial aspects of various methods, it has been observed that, regardless of the means used to improve autofocus accuracy, the light spot detected by the light sensor may undergo significant distortion when the test object is near the focus point.…”
Section: Introductionmentioning
confidence: 99%